2020
DOI: 10.13189/ujer.2020.082510
|View full text |Cite
|
Sign up to set email alerts
|

Values Education in Arabic Proverbs of Mahfudzat

Abstract: The purpose of this study is to find a general description of mahfudzat book, the core or content of Islamic education contained in mahfudzat and values contained in mahfudzat based on the Islamic perspective. The methods used are library research, and qualitative type, the approach used content analysis, descriptive, inductive, normative, and literature genetic structuralism approach. The general description of mahfudzat book includes several remarks of the Prophet, Companions of the Prophet, verses of wisdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Secondly, the study entitled Values Education in Arabic Proverbs of Mahfudzāt. The result of this research is that there are five aspects of education found in the Arabic proverbs, which are: creed, knowledge, deeds, morals, and social (Muthoifin and Nuha 2020). This research analysed values education in Arabic proverbs, yet it relates to the education values in this research that will be found in the Arabic novel 'Imarah Yacoubiyan.…”
Section: State Of the Arts And Distinguishmentioning
confidence: 96%
“…Secondly, the study entitled Values Education in Arabic Proverbs of Mahfudzāt. The result of this research is that there are five aspects of education found in the Arabic proverbs, which are: creed, knowledge, deeds, morals, and social (Muthoifin and Nuha 2020). This research analysed values education in Arabic proverbs, yet it relates to the education values in this research that will be found in the Arabic novel 'Imarah Yacoubiyan.…”
Section: State Of the Arts And Distinguishmentioning
confidence: 96%
“…Tidak bisa dipungkiri perilaku ini juga bisa terjadi diarea asrama yang memiliki peraturan yang memisahkan antara laki-laki dan perempuan dan kurangnya pengarahan, karena akan sangat mudah terjadinya pelaku penyimpangan ini. Faktor yang menjadikan pelaku ini ialah hanya memiliki ruang gerak yang kecil untuk berinteraksi terhadap lawan jenis dan kurangnya pengawasan [18].…”
Section: Faktor Pergaulan Dan Lingkunganunclassified